Origins of Religion, Cognition and Culture, edited by Armin W. Geertz. (9th November 2018) - Hampejs, Tomas
Abstract : Origins of Religion, Cognition and Culture, edited by Armin W. Geertz, Routledge, 2014. 429 pp. Hb., 161.62 USD ISBN: 978-1-84465-701-8